Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-10T16:53:26+01:00
A)4x-3=3x+5
4X-3x=5+3
x=8

b)5x+2=7-3x
5x+3x=7-2
8x=5//8
x=5/8

c)3(x-1)=0
3x-3=0
3x=3/3
x=1

e)-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-14-1
-10x=-15/-10
x=1 i 1/2


f)4(x-1)=6(1+x)
4x+4=6+6x
4x-6x=6+4
-2x=10//-2
x=-5
1 5 1
2010-02-10T16:54:55+01:00
A
4x-3=3x+5
4x-3x=5+3
x=8

B
5x+2=7-3x
5x+3x=7-2
8x=5 /:8
x=5/8

C
3(x-1)=0
3x-3=0
3x=3
x=1

D
-6(x+1)=24
-6x-6=24
-6x=18/:(-6)
x=-3

E
-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15
x=1 1/2( jedna cała i jedna druga)

F
4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10 /: (-2)
x= -5
2010-02-10T16:57:56+01:00
A)4x-3=3x+5|-3x
x-3=5|+3
x=8

b)5x+2=7-3x+3x
8x+2=7|-2
8x=5|8
x=0,625

c)3(x-1)=0
3x-3=0|+3
3x=3|:3
x=1